The night before [videorecording (DVD)] - Levine, Jonathan, 1976-; Rogen, Seth, 1982-; Gordon-Levitt, Joseph, 1981-; Mackie, Anthony, 1978-; Caplan, Lizzy, 1982-; Kaling, Mindy (Columbia Pictures, 2016)
Ethan, Isaac and Chris have been friends since childhood, and for a decade, their yearly Christmas Eve reunion has been an annual night of debauchery and hilarity. Now that they're entering adulthood, the tradition is coming to an end, and to make it as memorable as possible, they set out to find the Nutcracka Ball; the Holy Grail of Christmas parties.